Introduction. - Steiner, Shepherd; Dokurno, Karalyn (Mosaic: An Interdisciplinary Critical Journal, 2021)
An introduction is presented in which the editor discusses articles in the issue on topics including traditional site of artistic fundamental issue of topological projection, and lateralization of dialogue.